Three new species of the genus Dendronotus from Japan and Russia (Mollusca, Nudibranchia) - Martynov, Alexander; Fujiwara, Yoshihiro; Tsuchida, Shinji; Nakano, Rie; Sanamyan, Nadezhda; Sanamyan, Karen; Fletcher, Karin; Korshunova, Tatiana (Zootaxa, 2020)
Three new species of the genus Dendronotus are described from the North Pacific waters of Japan and Russia. For the first time since 1949, three new species, D. jamsteci sp. nov., D. zakuro sp. nov. and D. bathyvela sp. nov. are described from the waters of the Japanese Islands. D. zakuro sp. nov. was also discovered in the waters of Russia (Kamchatka). The descriptions of the new species D. jamsteci sp. nov. and D. zakuro sp. nov. are based on morphological and molecular data; D. bathyvela sp. nov. morphologically belongs to the group of D. robustus, D. velifer and D. patricki. This study revises our knowledge of North Pacific species of the genus Dendronotus, considerably expands the number of species worldwide and contributes to the multilevel fine-scale diversity concept.